Transition without transformation: the legacy of Sudan’s Comprehensive Peace Agreement - Carolan, Gene (International journal of transitional justice, 2020)
In recent years, the transitional justice framework has expanded to include a broader notion of transformative justice, which strives for socio-political reform in addition to legal accountability. Over the course of two civil wars, Sudan has grappled with various attempts at transition and transformation with mixed results. Though the 2005 Comprehensive Peace Agreement brought an end to decades of North-South conflict, South Sudan’s subsequent descent into civil war has been characterised by a flawed transition and a lack of any immediate transformative potential.This paper analyses the Comprehensive Peace Agreement’s transitional mechanisms. In doing so, it explores how certain mechanisms frame the ‘meta-conflict’ about what the conflict is about, and how this can cut off a range of conflict resolution opportunities. It concludes by considering the legacy of the Comprehensive Peace Agreement in contemporary Sudan and South Sudan, and how it might inform the prospective transitions in both countries.